[Letter] Maseno, Kisumu to His Excellency Sir J.A. Byrne, Governor of Kenya - Owen, Walter Edwin (Adam Matthew Digital, 1932)
Typescript letter from W.E. Owen, Archdeacon of Kavirondo, to J.A. Byrne, Governor of Kenya, in relation to the arrest of a parishioner, Jason Gor, accused of convening an illegal meeting in a Kavirondo church